Anatomia comparada da casca de stryphnodendron polyphyllum mart. (fabaceae) em cerrado sensu stricto e mata de galeria - Vergílio, Paula Cristina Benetton [UNESP] (2015)
The cerrado covers various vegetation types, among them, the cerrado sensu stricto, which is a savanna types where has the fire occurrence, and it has poorer soil, and the gallery forest, which is a forest type where has not the fire occurence, and it has rich soil. We hypothesized that the cerrado sensu stricto trees has ticker bark (fire protection), and it has a higher degree of scleromorphism into its cells (poorer soil). To test these hypotheses we compared populations of Stryphnodendron polyphyllum Mart. (Fabaceae) in both cerrado sensu stricto and gallery forest. We collected branche samples of adult trees of S. polyphyllum, and we performed the extraction and quantification of total phenols from the bark, and we made permanent and semipermanent bark slides, and we analyze the qualitative and quantitative bark aspects. The qualitative bark aspects did not show any variation between both populations, and it can be used for taxonomic purposes. The quantitative aspects showed variations between both populations. The cerrado sensu stricto population showed higher values in the width and proportion of rhytidome; and lower values in the width and proportion of conducting secundary phloem, and in the fiber diameter, and in the sieve element diameter, and in rays height. These differences highlight the strategies of each population. The feature bark of cerrado sensu stricto population is the fire protection, and phloem conductivity safety. The feature bark of gallery forest population is the phloem conductivity efficiency. We do not found differences neither of width and proportion bark, nor of degree of scleromorphic into bark cells between the study populations.